Reduced serum iron levels predict poor prognosis in pulmonary mucormycosis patients: a prospective, case‒control study - Qiongzhen Luo; Xinwei He; Jiao Xu; Li Li; Lina Zhao; Xiangdong Mu (Scientific Reports)
Abstract Pulmonary mucormycosis (PM) and invasive pulmonary aspergillosis (IPA) are both invasive pulmonary fungal infections with similar clinical manifestations. Few studies have focused on the expression of serum iron in patients with PM and IPA. A prospective, case‒control study was conducted between January 2023 and December 2024. Patients diagnosed with PM or IPA were assigned to the PM group or the IPA group, respectively. Clinical data were recorded for all enrolled patients. Serum iron, serum ferritin, unsaturated iron-binding capacity (UIBC), total iron-binding capacity (TIBC), and percentage transferrin saturation levels were determined via an automatic biochemical detector. A total of 58 patients with PM and 49 patients with IPA were enrolled. Nine patients in the PM group and one patient in the IPA group died during hospitalization. The serum iron, UIBC, and TIBC levels in the PM group were significantly lower than those in the IPA group (all p < 0.05). The serum ferritin level was significantly greater in the PM group than in the IPA group (p = 0.021). Binary logistic regression analysis revealed that only the TIBC level was an independent risk factor for PM [OR (95% CI) = 0.892 (0.839–0.947), p < 0.001]. Cox proportional hazards regression analysis revealed that the serum iron concentration [HR (95% CI) = 0.872 (0.784–0.969); p = 0.011] was an independent predictor of mortality risk in PM patients. Lower TIBC levels at admission were associated with a greater risk of PM, and reduced serum iron levels predict poor prognosis in patients with PM. Using IPA patients as controls, we preliminarily revealed aberrant iron metabolism in PM patients. Trial registration: ClinicalTrials.gov ID NCT06495905, Date of registration July 11, 2024 (retrospectively registered).